The Cambridge companion to the literature of Berlin - Webber, Andrew (Cambridge Cambridge University Press, 2017)
"This collection of essays by international specialists in the literature of Berlin provides a lively and stimulating account of writing in and about the city in the modern period. The first eight chapters chart key chronological developments from 1750 to the present day, while subsequent chapters focus on Berlin drama and poetry in the twentieth century and explore a set of key identity questions: ethnicity/migration, gender (writing by women), and sexuality (queer writing). Each chapter provides an informative overview along with closer readings of exemplary texts. The volume is designed to be accessible for readers seeking an introduction to the literature of Berlin, while also providing new perspectives for those already familiar with the topic. With a particular focus on the turbulent twentieth century, the account of Berlin's literary production is set against broader cultural and political developments in one of the most fascinating of global cities"--Provided by publisher.
Machine generated contents note: Introduction Andrew J. Webber; 1. Literature and the Enlightenment / Matt Erlin; 2. Romantic sociability, aesthetics and politics / Jurgen Barkhoff; 3. Literary realism and naturalism / John B. Lyon; 4. Short prose around 1900 / Anne Fuchs; 5. Modernist writing and visual culture / Carolin Duttlinger; 6. Writing under National Socialism / Reinhard Zachau; 7. Writing in the Cold War / Alison Lewis; 8. Writing after the Wall / Katharina Gerstenberger; 9. Women writers and gender / Lyn Marven; 10. Queer writing / Andreas Krass and Benedikt Wolf; 11. Berlin as a migratory setting / Yasemin Yildiz; 12. Modern drama and theatre / David Barnett; 13. Twentieth-century poetry / Gerrit-Jan Berendse.
Includes bibliographical references and index.
Keywords: German literature -- Germany -- Berlin -- History and criticism; Berlin (Germany) -- In literature